2015
DOI: 10.1159/000382080
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hormonal Profile on Resting Metabolic Rate in Normal, Overweight and Obese Individuals

Abstract: Aims: To investigate whether blood thyroid stimulating hormone (TSH), cortisol, insulin and glucose concentrations (plus glucose:insulin ratio; GIR) could improve the accuracy of resting metabolic rate (RMR) prediction in normal, overweight and obese persons. Methods: Predictive equations were developed and compared against indirect calorimetry measures for RMR in 217 weight-control clinic participants (n = 128 males and n = 89 females: ∼24% normal weight, ∼39% overweight and ∼37% obese). Results: Using the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…While the exact contributing factors to these differences are still under debate, differences in hormonal status are likely a strong contributor, especially in premenopausal women. Hormones such insulin, leptin, estradiol, and cortisol vary with body fat distribution and are important regulators of energy balance and substrate availability [16,17]. In the current study, a higher RMR was associated with cortisol and estradiol in men, while insulin was associated with RMR in women.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…While the exact contributing factors to these differences are still under debate, differences in hormonal status are likely a strong contributor, especially in premenopausal women. Hormones such insulin, leptin, estradiol, and cortisol vary with body fat distribution and are important regulators of energy balance and substrate availability [16,17]. In the current study, a higher RMR was associated with cortisol and estradiol in men, while insulin was associated with RMR in women.…”
Section: Discussionsupporting
confidence: 46%
“…In the current study, a higher RMR was associated with cortisol and estradiol in men, while insulin was associated with RMR in women. It is known that insulin and cortisol are important regulators of glucose metabolism [17], but previous studies have reported weak correlations between insulin, cortisol, and RMR [18,17,6]. Female-specific associations between insulin and RMR have been previously reported by Astrup et al [6] (R=0.47) and Wright et al [17] (R=0.35), but both studies reported little benefit for predicting metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BMR, which is a character of the resting metabolism and is exactly associated with obesity [3]. Researchers recommended a new predictive equation for estimating resting metabolic rate (RMR) using demographics (race, age, height, weight, gender), and other biological indices (adipose tissue, fat-free mass) [4-6]. In addition, vitamin D status has been found to be a new independent predictor of RMR in adults [7].…”
Section: Introductionmentioning
confidence: 99%